The Effects of Macroeconomic Factors and Singapore and Thailand Stock Indices on The Volatility of the Jakarta Composite Index - Situmorang, Trisna Vela; Kaluge, David (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This research examines the influence of domestic and external macroeconomic factors on stock market volatility in Indonesia, particularly the Jakarta Composite Index (JCI). While stock market volatility has become a global concern, there remains a research gap regarding the impact of regional global factors—such as neighboring countries' stock indices—on JCI volatility. The main objective of this research is to analyze the effects of inflation, exchange rate, and trade balance as domestic factors, alongside the Singapore stock index (Straits Times Index) and Thailand stock index (Stock Exchange of Thailand) as external factors, and S&P 500 and foreign exchange reserves as control variables, on JCI volatility over the period 2014–2023. The study employs the Autoregressive Distributed Lag (ARDL) method using monthly data. The results show that in the long term, the exchange rate and the SET index have a significant effect on JCI volatility, while in the short term, only the exchange rate shows a significant impact. Other factors do not demonstrate a consistent significant influence. These findings highlight the importance of exchange rate stability and regional stock market dynamics in influencing domestic stock market fluctuations.